AN ANALYSIS ON STUDENTSâ DIFFICULTIES IN THE USE OF PLURAL â-Sâ FORM AND SIMPLE PRESENT MARKER â-Sâ - Astriyanti, Diah (Jurnal Pendidikan Bahasa, 2016)
This research entitled An Analysis on Studentsâ Difficulties in the use of Plural â-sâ Form and Simple Present Marker â-sâ are to identify the difficulties that the students face in using marker âs in plural form and in simple present tense. This research method was a descriptive research with the sample the first semester students of Mathematic Education study program. The sample of this research consist of 56 students from class A morning and 22 students from class B morning, so the total sample were 78 students. The tools used in the research were aÂ test and a questionnaire. From the data analysis it was found that the students average score was 45.6 which categorized as poor. The score then indicates that the students have difficulties in the use ofÂ plural â-sâ form and simple present tense marker â-sâ. The result from questionnaire also showed that more than 60% agree that the students face difficulties in using marker âs in plural form and infinitive in simple present tense.Keywords: Studentsâ Difficulties, Plural â-sâ Form, Simple Present Marker â-sâ